The Role of Alveolo-Arterial Oxygen Gradient and Pneumonia Severity Index in Predicting Mortality in Patients with Coronavirus Disease-19 Pneumonia - Kefeli̇ Çeli̇k, Hale; Doğanay, Zahide; Sezer Akman, Tuğçehan (Ondokuz Mayıs Üniversitesi, 2022)
Purpose of the study is to determine the success rates of alveolo-arterial oxygen gradient (AaDO2) and the pneumonia severity index (PSI) in predicting mortality for the patients diagnosed with COVID-19 pneumonia. This retrospective study included patients who were treated with the diagnosis of COVID-19 pneumonia in the ICUs. Demographic characteristics, arterial blood gas values, radiological images and laboratory data of the patients were used through the hospital database and patient files. Group I patients consist of alive and Group II patients consist of deceased persons. 150 of 263 patients included in this study are in Group I and 113 are in Group II. RT-PCR test was positive in 20.9% of the patients. The most common symptom was dyspnea with 76.5% and the most common additional disease was hypertension with 58.1%.65% of patients had radiological involvement in both lungs, and the most common finding was the ground-glass opacity at 70.7%.In predicting mortality, PSI value was 135 in group I and 174 in group II (p
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi; alveolo-arterial oxygen gradient; COVID-19; mortality; pneumonia severity index; 3. Good health